Review of Maritime Transport 2019 - United Nations Conference on Trade; Development (United Nations, 2019)
This report provides a concise update of key data relating to the maritime transport sector, spanning demand and supply, performance, as well as transversal issues ranging from regulatory and legal developments affecting maritime transport and technological developments/innovation, with the theme being “Sustainable Shipping”. Around 80 per cent of the volume of international trade in goods is carried by sea, and the percentage is even higher for most developing countries. The Review provides an analysis of structural and cyclical changes affecting seaborne trade, ports and shipping, as well as an extensive collection of statistical information.